Analysis of Green Open Space Changes at Gunung Gede - Cilibende Campus Using Geographic Information System - Prawira, Gilang Indracakti; Sutoyo; Putra, Heriansyah (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
IPB Gunung Gede - Cilibende Campus is one part of IPB University which is used by IPB Vocational School and IPB Business School. With limited land, the increase in the number of students and lecturers, as well as the development of campus infrastructure and facilities has the potential to increase carbon emissions on campus. So it is necessary to have a green space that acts as a carbon dioxide (CO2) absorber and creates a healthier environment at IPB Gunung Gede - Cilibende Campus. This study aims to analyze land use, and changes in green space at IPB Gunung Gede Campus - Cilibende. Processing involved secondary data of satellite imagery of IPB Gunung Gede - Cilibende Campus in 2019-2023 collected from Google Satellite using Google Earth Pro. Digitization was carried out to determine the land use area in calculating the green space ratio and the minimum green space requirement. Land use at IPB Gunung Gede - Cilibende Campus consists of forests, plants, buildings, parking areas, and roads. The percentage of green space in 2019 amounted to 64.05% until 2023 to 45.13%, smaller than the minimum green space requirement of 58%. The Green Roof concept can be applied as a business activity to increase green land area. By applying the Green Roof concept, IPB Gunung Gede - Cilibende Campus gets an additional green open space of 16.5% so the total green space ratio in 2023 becomes 61.63%.